The Association Between Neutrophil/Lymphocyte Ratio and Disease Activity in Rheumatoid Arthritis and Ankylosing Spondylitis - Mercan, Ridvan; Bitik, Berivan; Tufan, Abdurrahman; Bozbulut, Utku Burak; Atas, Nuh; Ozturk, Mehmet Akif; Haznedaroglu, Seminur; Goker, Berna (Journal of clinical laboratory analysis, 2016)
Background Elevated neutrophil count is associated with poor prognosis and increased mortality in many conditions. Neutrophil to lymphocyte ratio (NLR) has emerged as a marker of inflammation in neoplastic and cardiovascular disorders. Herein, we investigated utility of this simple tool in rheumatoid arthritis (RA) and ankylosing spondylitis (AS). Methods The study consisted of 136 RA and 140 AS patients, along with 117 healthy control subjects. RA and AS activities were determined with Disease Activity Score (DAS) and Bath Ankylosing Spondylitis Disease Activity indices (BASDAI), respectively. The association between NLR and disease activity was analyzed. Results Erythrocyte sedimentation rate (ESR), C‐reactive protein (CRP), and neutrophil counts were significantly higher in RA and AS patients compared to healthy controls. Similarly, NLR was higher compared to control subjects, both in RA (2.53 ± 1.4 vs. 2.16 ± 1.0, P = 0.019) and AS (2.43 ± 1.4 vs. 2.16 ± 1.0, P = 0.077). NLR correlated well with ESR and CRP, both in RA and AS. Moreover, NLR increased across worsening DAS28 activity groups (2.1 ± 1.0 in patients with remission, 2.5 ± 1.0 in low–moderate, 3.8 ± 2.5 in high disease activity). However, no association was found between NLR and BASDAI. Conclusion NLR is a cheap and readily available marker for the assessment of disease activity in RA.